Hadith Studies in the Indonesian Context: The Integration of Pesantren and Modern Academic Epistemologies - Asrowi, Hanan; Rozy, Fachrul (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Hadith studies in Indonesia have developed through two parallel epistemological traditions: the pesantren tradition rooted in sanad transmission and turāth literature, and the modern academic tradition within Islamic Higher Education Institutions (PTKI), which emphasises scientific criticism and interdisciplinary analysis. This dual development reflects society’s need for a locally relevant yet globally standardised understanding of hadith. Objective: This study aims to analyse the epistemological construction of hadith studies in Indonesia by examining their historical development, the epistemological characteristics of pesantren and PTKI traditions, and their integrative model in shaping contemporary hadith scholarship. Method: A qualitative descriptive approach was employed through library research, utilising historical analysis, content analysis, and comparative analysis of relevant literature from both traditions. Results: The integration of hadith epistemology does not occur through formal curriculum unification, but through the intellectual mobility of scholars and academics who transfer pesantren-based sanad methods into modern academic contexts. This process creates a distinctive scholarly pattern that combines the rigour of traditional transmission with critical academic approaches, producing contextual and applicable hadith studies. Conclusion: The epistemology of hadith studies in Indonesia demonstrates a flexible, mutually enriching integrative model that strengthens both moral and intellectual legitimacy at the national and global levels. Contribution: This study contributes to the development of a conceptual framework that can inform curriculum design, educational strategies, and future research in hadith studies and Islamic scholarship.